Edible insects and legumes exert an antioxidant effect on human colon mucosal cells stressed with 2,2′-azobis (2-amidinopropane)-dihydrochloride - D’Antonio, Veronica; Battista, Natalia; Di Mattia, Carla D.; Sacchetti, Giampiero; Ramal-Sanchez, Marina; Prete, Roberta; Angelino, Donato; Serafini, Mauro (Frontiers in Nutrition, 2023)
Edible insects have been recognized as a more sustainable source of nutrients and bio-active compounds than animal-based products, in line with classical vegetable sources such as legumes. In this study, we assessed the antioxidant properties of four edible insects (silkworms, grasshoppers, mealworms and giant worms) and four legume seeds (lentils, chickpeas, Roveja peas and grass peas).After the aqueous extraction or in vitro simulated digestion process, selected products were assessed for: i) in vitro antioxidant capacity through Ferric Reducing Antioxidant Power (FRAP) assay; ii) the ability to reduce free radicals production induced by a pro-oxidant agent in cells of human colonic mucosa. Results showed that all the aqueous extracts and digesta of edible insects displayed significantly higher in vitro antioxidant activity than legumes. Moreover, edible insects at all tested concentrations were able to exert an antioxidant effect in the cellular model, while legumes were effective mainly at high concentrations. Despite human trials are need to confirm and define these results in a physiological situation, here we suggest a role for edible insects in oxidative stress prevention. Since oxidative stress is strongly correlated with several intestinal pathologies, the results obtained could be interesting for the prevention and relief of the negative symptoms, offering new advantages to their already known ecological and nutritional properties.AA, treatment with ABAP 250 μM and ascorbic acid 2 μM; ABAP, 2,2′-azobis 2-amidinopropane dihydrochloride; ANOVA, analysis of variance; AUC, area under the curve; C-, vehicle (negative control); C+, treatment with ABAP 250 μM (positive control);